Comparison of electrostatic charge and beta attenuation mass monitors for continuous airborne PM10 monitoring under field conditions - Intra P. (2017)
© 2016, Korean Institute of Chemical Engineers, Seoul, Korea. An electrostatic PM10 mass monitor (EPMM) used for wireless continuous airborne particulate matter monitoring was developed and evaluated in our previous work. However, differences in measured PM10 mass concentrations between the electrostatic charge and the beta ray attenuation methods due to the frequent occurrence of high humidity and temperature in the ambient air in Thailand’s have not been extensively studied in our previous work; and in the literature, it would be necessary to compare the output of the EPMM against the beta ray attenuation mass monitor. In this study, we evaluated the performance of the EPMM simultaneously with a commercially available FH62C14 Beta gauge continuous ambient particulate monitor, Thermo Fisher Scientific Inc., for PM10 measurements at ambient condition in the field. The measurements were made at Yupparaj Wittayalai School, Si Phum, Mueang, Chiang Mai, Thailand from November 16-23, 2015. They showed that the averages of PM10 mass concentrations measured by the EPMM linearly correlate very well with the PM10 mass concentrations measured by the FH62C14. The slopes were 0.9620 and 1.0649 for 1 and 24-hour, respectively, and R 2 of 0.8634 and 0.9889 for 1 and 24-hour, respectively. Finally, this comparison proved to be particularly useful in the refinement and design of the EPMM.